Microbial Diversity and Biotechnology in Food Security 2014
DOI: 10.1007/978-81-322-1801-2_16
|View full text |Cite
|
Sign up to set email alerts
|

An Impact of Seed Priming on Disease Resistance: A Review

Abstract: Seed priming is basically a physiological seed quality enhancement method which offers a hydration treatment that allows controlled imbibition and induction of the pre-germinative metabolism (activation), but radicle emergence is prevented. The beneficial effects of this technology are greater cellular membrane integrity, counter action of lipid peroxidation, antipathogenic effects, repair of biochemical lesions by the cellular enzymatic repair system and the metabolic removal of toxic substances. Disease is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…We only planted in the field three species, A. saman, E. cyclocarpum, and S. macrophylla. The C. odorata seedlings died in the shade house because of damping off, although it has been reported that priming induces resistance to seedling diseases (Mondal & Bose, 2014). Species' distribution and diversity in the tropical forests can be related to their tolerance to high or low soil water potential (Born et al, 2015).…”
Section: Seedling Growth In the Shade House And Survival In The Fieldmentioning
confidence: 99%
“…We only planted in the field three species, A. saman, E. cyclocarpum, and S. macrophylla. The C. odorata seedlings died in the shade house because of damping off, although it has been reported that priming induces resistance to seedling diseases (Mondal & Bose, 2014). Species' distribution and diversity in the tropical forests can be related to their tolerance to high or low soil water potential (Born et al, 2015).…”
Section: Seedling Growth In the Shade House And Survival In The Fieldmentioning
confidence: 99%
“…Seed priming has been recognized as a promising method to improve the physiological quality of the seed and to enhance resistance against pathogens (Mondal and Bose, 2014). Recently, preliminary results have shown that the incubation of tobacco seedlings in a 1.3 µM BcIEB1 solution for 2 weeks conferred resistance to B .…”
Section: Resultsmentioning
confidence: 99%
“…An interesting result obtained with the priming treatments was that the few seedlings obtained from the control seeds of both seed lots underwent high mortality due to damping‐off; a similar result was observed by Benítez‐Rodríguez et al (). By contrast, the primed seedlings had high survival, most likely because priming induces resistance to seedling diseases or antipathogenic effects (Mondal & Bose ).…”
Section: Discussionmentioning
confidence: 99%